Dynamic control of a light-emitting diode system based on the general photo-electro-thermal theory - Qin,YX; Lin,DY; Chung,HSH; Yan,W; Hui,SYR (2009 IEEE Energy Conversion Congress and Exposition Ecce 2009, 2009)
This paper presents a dynamic thermal model of a LED system and a control strategy for optimal power point tracking (OPPT). The control strategy is based on the general theory which links the photometric, electric and thermal behaviors of LEDs together. The control implementation enables the optimal operating of the LED systems to be determined dynamically. By measuring the ambient temperature and the heatsink temperature of LED system, the proposed control scheme allows the LED system to operate at the optimal dynamic operating points at which maximum luminous flux is generated. Practical tests have been carried out to verify the model and the general theory. © 2009 IEEE.